CILLA TECH PARK AND THE CONSTRUCTION OF INNOVATIVE ENVIRONMENTS: STRATEGIES FOR REGIONAL DEVELOPMENT - Vecchia, Raquel Virmond Rauen Dalla; da Silva, Eduardo Lucano (Seven Editora, 2025)
Recent technological transformations have fueled debate on regional development policies, highlighting innovation as a central element. In this context, technology parks emerge as strategic instruments for fostering innovation ecosystems, fostering economic and social development. This study analyzes the creation of Cilla Tech Park (CTP), located in Guarapuava, Paraná, as an example of a public policy focused on regional innovation. The qualitative, descriptive, and exploratory research was conducted through a case study, based on a literature review, document analysis, and institutional data. The results highlight the articulation between government, universities, and the productive sector—the triple helix model—as a determining factor in the consolidation of the local innovation ecosystem. The CTP stands out as an environment conducive to knowledge generation, entrepreneurship, and technology transfer, contributing significantly to the region’s economic dynamism. Guarapuava’s experience demonstrates how well-structured public policies, combined with cooperation among local stakeholders, can drive sustainable development and regional competitiveness. DOI: https://doi.org/10.56238/sevened2025.029-031